(3Yde GdfaS GdGLJeGYj (B/s - (3LhOI Hfj, LGHQs ((3GdCQOf (B:s (3OGQ GdKbGaI ,s, 2015)
(3GMJhi gPG GdcJGH Ydi GMOi YTQI hMOI JfGhdJ GdJYQja HYde GdfaS GdGLJeGYj h efGgL GdHMK ajg h YedjI Gdfeh h GdJfTFI GdGLJeGYjI h GdJaGYd h GdJZjQ h GdGJUGd GdGLJeGYj h GdbjGOI GdGLJeGYjI ceG JWQbJ Edi GdTNUjI h HfGJgG h fXQjGJgG hJWQbJ GjVG Edi GdOGaYjI h GdGJLGgGJ h Gdbje h GdMQH GdfaSjI h GdGfMQGaGJ h GdGeQGV GdGLJeGYjI (B.s
Keywords: (3Yde GdELJeGYs; (3Yde GdfaSs; (3Yde GdfaS GdELJeGYjs